Comparison of CMV pp65 Antigen and IgM Antibody Detection for Early Recognition of CMV Primary Infection and Reactivation (Mymensingh Medical Journal, 2008)
Mymensingh Med J. 2008 Jan;17(1):28-31.The abstract of this article is available on the PubMed website